The missing tarts - Hennessy, B. G. (Barbara G.); Pearson, Tracey Campbell (New York : Viking Kestrel, 1989)
When the Queen of Hearts discovers that her strawberry tarts have been stolen, she enlists the help of many popular nursery rhyme characters in order to find them.
Wilson's Children
School Library Journal starred
Booklist starred
3.8
K-3
Keywords: Kings, queens, rulers, etc. -- Fiction; Characters and characteristics in literature -- Fiction; Stories in rhyme; Queens -- Fiction; Characters and characteristics in literature -- Fiction; Stories in rhyme